2011
DOI: 10.1111/j.1750-3841.2011.02181.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Starter Culture and Storage on the Flavor of Liquid Whey

Abstract: Lipid oxidation products are primary contributors to whey ingredient off-flavors. Flavor plays a critical and limiting role in widespread use of dried whey ingredients, and enhanced understanding of flavor and flavor formation in fluid whey are industrially relevant. Results from this study demonstrate that oxidation occurs in milk prior to cheesemaking but that starter type and starter strain influence also oxidative stability and lipid oxidation off flavors in fluid whey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 18 publications
9
52
0
Order By: Relevance
“…Attributes were scored using a 0‐ to 15‐point universal Spectrum™ intensity scale where 0 = absence of the attribute and 15 = extremely high intensity of attribute. Most whey protein flavors fall between 0 and 4 (Campbell and others 2011a, 2011b). LSD = least significant difference. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Attributes were scored using a 0‐ to 15‐point universal Spectrum™ intensity scale where 0 = absence of the attribute and 15 = extremely high intensity of attribute. Most whey protein flavors fall between 0 and 4 (Campbell and others 2011a, 2011b). LSD = least significant difference. …”
Section: Resultsmentioning
confidence: 99%
“…Karagul‐Yuceer and others (2003) identified aroma‐active compounds in liquid Cheddar wheys including 2,3‐butanedione, 2‐butanol, hexanal, 2‐acetyl‐1‐pyrroline, methional, ( E,E )‐2,4‐nonadienal, ( E,E )‐2,4‐decadienal, and other short‐chain volatile acids. Campbell and others (2011b) documented differences in volatile compound profiles of Cheddar wheys from different mesophilic starter cultures and also demonstrated that higher concentrations of lipid oxidation products were noted in Cheddar whey compared to Mozzarella whey. Gallardo‐Escamilla and others (2005) evaluated several different types of liquid whey by sensory and headspace analysis but did not identify the distinguishing aroma‐active compounds.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations